Anti-rheumatic drug-induced hepatitis B virus reactivation and preventive strategies for hepatocellular carcinoma. (April 2022) - Zhou, Qiao; Zhang, Qi; Wang, Kaiwen; Huang, Ting; Deng, Shaoping; Wang, Yi; Cheng, Chunming
Abstract: To date, an estimated 300 million people worldwide have been infected with chronic hepatitis B virus (HBV). Although anti-HBV therapies have improved the long-term survival profile of chronic carriers, viral reactivation still poses a significant challenge for preventing HBV-related hepatitis, hepatocellular carcinoma (HCC), and death. Immuno-modulating drugs, which are widely applied in managing rheumatic conditions, are commonly associated with HBV reactivation (HBVr) as a result of drug-induced immune suppression. However, there are few reports on the risk of HBVr and the medication management plan for HBV carriers, especially rheumatic patients. In this review, we summarize immuno-modulating drug-induced HBVr during rheumatoid therapy and its preventive strategies for HBVr-induced liver diseases, especially cirrhosis and HCC. These findings will assist with developing treatments for rheumatic patients, and prevent HBV-related cirrhosis and HCC. Graphical Abstract: Life cycle of HBV and the effect of DMARDs on HBV reactivation. Life cycle of HBV and HBV immune evasion is shown. Sulfasalazine, tacrolimus, and IL-6 prevent the virus from entering the cell by inhibiting sodium taurocholate cotransporting polypeptide (NTCP). Glucocorticoids and Cyclophosphamide increase the replication from cccDNA. IL-6 and mycophenolate mofetil inhibit the replication from cccDNA. Leflunomide promotes virus replication through increasing phosphorylation of mitogen-activated protein kinase (MAPK) p38. TNF-α degrades cccDNA by activating Apobec protein. Hydroxychloroquine, thalidomide, and TNFα inhibitor downregulate TNFα, thus decreasing viral clearance. Dendritic cells capture HBV antigens and present them to naïve T cells, where IL-23 (inhibited by Ustekinumab and Guselkumab) induces naïve T cells to differentiate into Th17 cells. IL-17 (inhibited by Secukinumab) secreted from Th17 cells induces B cell differentiation, secreting specific antibodies to neutralize the free HBV. Naïve T cells differentiate into Th1 cells induced by IL-12 (inhibited by Ustekinumab) and Th1 cells are induced by IFN-γ (inhibited by Tofacitinib and Baricitinib) to become Tc cells (inhibited by TNFα). Both Th1 and Tc cells can inhibit HBV. ga1